2015
DOI: 10.3390/ijerph120910635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Personal Exposure to PM2.5 on Respiratory Health in a Mexican Panel of Patients with COPD

Abstract: Background: Air pollution is a problem, especially in developing countries. We examined the association between personal exposure to particulate matter with an aerodynamic diameter less than 2.5 µm (PM2.5) on respiratory health in a group of adults with chronic obstructive pulmonary disease (COPD). Methods: All participants resided in Mexico City and during follow-up, personal exposure to PM2.5, respiratory symptoms, medications, and daily activity were registered daily. Peak expiratory flow (PEF) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 45 publications
1
24
1
2
Order By: Relevance
“…These results are close to the study conducted by Chattopadhyay BP et al, who found that the impaired pulmonary function was associated with exposure to automobile exhaust, especially, 30.4% at risk of developing the restrictive syndrome for conductors and 28.9% for drivers [ 30 ]. Similar results in the decrease of pulmonary function associated to traffic-related air pollution were reported in Mexican, Indian and in Danish studies [ 31 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…These results are close to the study conducted by Chattopadhyay BP et al, who found that the impaired pulmonary function was associated with exposure to automobile exhaust, especially, 30.4% at risk of developing the restrictive syndrome for conductors and 28.9% for drivers [ 30 ]. Similar results in the decrease of pulmonary function associated to traffic-related air pollution were reported in Mexican, Indian and in Danish studies [ 31 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…5). Nevertheless, the impact of BC on S. pneumoniae colonisation may explain why exposure to PM is associated with bacterial pneumonia (Brugha and Grigg, 2014;MacIntyre et al, 2014;Qiu et al, 2014) and exacerbation of chronic infectious diseases such as asthma and COPD (Cortez-Lugo et al, 2015;Deng et al, 2015;Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Having Amerindian genes is more commonly associated with COPD-BS and that may be linked with genetic susceptibility, contrasting with increased exposure to particulate matter in tobacco smokers and also with more exposure to air pollution in the city, which could influence our results. Moreover, usually there is more intense exposure to PM2.5 in tobacco smokers compared to individuals exposed to biomass smoke COPD [29]. The composition of tobacco biomass and wood or fuel biomass may explain differences in the presentation of both forms of COPD [2][3][4]6,25].…”
Section: Discussionmentioning
confidence: 99%